Participation of feed industry personnel and pig farms to reduce risk of disease spread between farms - Bottoms, K.; Dewey, Catherine E.; Richardson, K.; Poljak, Z.; Carter, N. (2014)
Biosecurity protocols reduce the introduction and spread of pathogens among swine farms. For pigs, biosecurity ensures market stability, maintains export opportunities, and controls spread of production and public health diseases. Salmonella, the second most common cause of bacterial foodborne illness, causes gastrointestinal illness. Pigs can be asymptomatic carriers of the bacteria and pork products are a known source of salmonellosis in humans. Salmonella have been isolated from pigs, boots, flies, rodents, bird feces, feed, feed-ingredients, and feed trucks. Objective: to identify management factors to reduce the risk of disease spread among swine farms through feed trucks. Methods: Focus groups and key informant interviews were conducted with managers, dispatchers and drivers of feed companies and swine producers. Participants rated the factors for economic and logistical feasibility and likelihood of reducing disease spread. Highly rated factors were used in a field trial. In total, 40 drivers from 3 companies, delivering feed to 2202 farms over 6 weeks (in the winter) collected descriptive data on the factors and compared use of different boots. Farm factors (prevalence) were: keeping areas (driveway, feed bin and barnyard) clean of mud and manure (82%), and dead-stock (91%); having an outbuilding to deliver bagged feed (24%); providing farm boots and coveralls for the driver; ordering the correct amount of feed; and notifying feed mill of a disease outbreak. Feed truck driver factors included wearing new clean, disinfected, dried boots (25%) and gloves (50%) at each farm; remaining outside the barn (92%); washing the steering wheel (49%), floor mat (77%) and outside of the truck (32%) every 24 hours; following farm protocols; and leaving feed bill outside barn (54%). Drivers given disinfected rubber boots were more likely to wear these on farms (42%) than plastic disposable boots (4%) (P<0.05). Biosecurity is a responsibility that is shared among all members of the industry. Feed personnel were encouraged to know more about disease transmission.